The Impact of Geo-blocking Ban on the Development of the European Digital Single Market - Dumitru, Ovidiu Ioan; Stoican, Andreea (Technium Social Sciences Journal, 2020)
The ban of geo-blocking intervened in recent years within the borders of the European Union and it represents not only a control and even an elimination of the discrimination regarding the nationality of the customers on the on-line trade, but also a mean of gaining important economic benefits for all the participants and countries involved. The current study aims in presenting and analyzing the importance and necessity of the existence of a set of legal documents that focus on eliminating the unjustified geo-blocking in the e-commerce, as well as the benefits such measures bring not only at the level of the economy of each Member State, but also the impact upon the customers - as important participants to the digital single market-, products and pricing.